Comparative experimental subcutaneous glanders and melioidosis in the common marmoset (Callithrix jacchus). Issue 6 (5th December 2014) - Nelson, Michelle; Salguero, Francisco J.; Dean, Rachel E.; Ngugi, Sarah A.; Smither, Sophie J.; Atkins, Timothy P.; Lever, Mark S.
Summary Glanders and melioidosis are caused by two distinct Burkholderia species and have generally been considered to have similar disease progression. While both of these pathogens are HHS/CDC Tier 1 agents, natural infection with both these pathogens is primarily through skin inoculation. The common marmoset (Callithrix jacchus) was used to compare disease following experimental subcutaneous challenge. Acute, lethal disease was observed in marmosets following challenge with between 26 and 1.2 × 108 cfu Burkholderia pseudomallei within 22–85 h. The reproducibility and progression of the disease were assessed following a challenge of 1 × 102 cfu of B. pseudomallei. Melioidosis was characterised by high levels of bacteraemia, focal microgranuloma progressing to non‐necrotic multifocal solid lesions in the livers and spleens and multi‐organ failure. Lethal disease was observed in 93% of animals challenged with Burkholderia mallei, occurring between 5 and 10.6 days. Following challenge with 1 × 102 cfu of B. mallei, glanders was characterised with lymphatic spread of the bacteria and non‐necrotic, multifocal solid lesions progressing to a multifocal lesion with severe necrosis and pneumonia. The experimental results confirmed that the disease pathology and presentation is strikingly different between the two pathogens. The marmoset provides a model of the human syndrome for both diseases facilitating the development of medical countermeasures.